Age‐specific risk of renal graft loss from late acute rejection or non‐compliance in the adolescent and young adult period. Issue 6 (10th June 2018) - Ritchie, Angus G.; Clayton, Philip A.; McDonald, Stephen P.; Kennedy, Sean E.
Abstract: Aims: The aims of this study were to identify if an age‐specific high‐risk window for graft loss is present in Australia and New Zealand and identify the aetiology for such graft loss using the Australia and New Zealand Dialysis and Transplant Registry. Methods: Retrospective cohort analysis of all renal transplants were performed in Australia and New Zealand during 1985–2010 in which the graft survived >3 months and the patient spent at least some time aged 10–30 years inclusive while the graft was functioning. Adjusted hazard ratio (aHR) for graft loss according to age, sex, race, cause of end‐stage kidney disease, transition, era of transplantation, donor type and human leucocyte antigen mismatch were calculated using an extended Cox proportional hazards model for graft loss from any cause and graft loss from late acute rejection (LAR) or non‐compliance. Results: A total of 3289 grafts in 3048 recipients were included. A total of 757 grafts failed including 110 (15 %) from LAR or non‐compliance. Age was strongly associated with graft loss from LAR or non‐compliance ( p  < 0.001). Compared with age 10–12 years, the risk of graft loss from LAR or non‐compliance was significantly increased from 16–24 years, peaking at 19–21 years (aHR 11.3, 95% confidence interval (CI) 1.5–84.3, p  < 0.001). Indigenous race was associated with LAR or non‐compliance (aHR 3.5, 95% CI 2.1–5.6) whereas paediatric‐to‐adult transition with a functioning transplant was not (aHR 1.2, 95% CI 0.4–3.5, p  = 0.68). Conclusion: The high risk of graft loss during adolescence and young adulthood is primarily due to LAR or non‐compliance. The elevated risk continues well into the 20s and is independent of paediatric‐to‐adult transition. Summary at a Glance: The manuscript highlights important issues relating to kidney transplant outcome during the young adolescent and the early adulthood period. Accepting the limitations of the study which uses registry acquired data, the manuscript demonstrates significant graft loss throughout the time period relating to age; however, transition from paediatric care to young adulthood was not a specific risk factor.